Budaya Organisasi yang Mendukung Keselamatan Pasien di Rumah Sakit - Ari Widyanti (Institute of Research and Community Outreach - Petra Christian University, 2016)
Organizational culture is one of important factors that contribute to the performance of an organization, including in a hospital. In a hospital, performance can be measured by its level of patient safety. Howover, studies and research that discuss the relationship of organizational culture and patient safety are still very limited, including in Indonesia. This research is conducted to observe organizational culture that support patient safety. This research is conducted in three hospitals in Jakarta. Type of organizational culture is identified using the Organizational Culture Assessment Instrument (OCAI) questionnaire and the level of patient safety is assessed using the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. Once the organizational culture is identified and the level of patient safety culture is observed in each hospital, correlation test and analysis is conducted between types of organizational culture with aspect of patient safety based. Results show that three hospitals do not have dominant organizational culture. However, type of organizational culture that has a significant positive correlation with aspect of patient safety the most is adhocracy culture, eventhough other organizational culture type also support patient safety. The result of this research then used as initial suggestion to make change on organizational culture so that patient safety could be improved.